1992
DOI: 10.1128/aem.58.8.2616-2624.1992
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of phenazine antibiotic biosynthesis to the ecological competence of fluorescent pseudomonads in soil habitats

Abstract: Phenazine antibiotics produced by Pseudomonas fluorescens 2-79 and Pseudomonas aureofaciens 30-84, previously shown to be the principal factors enabling these bacteria to suppress take-all of wheat caused by Gaeumannomyces graminis var. tritici, also contribute to the ecological competence of these strains in soil and in the rhizosphere of wheat. Strains 2-79 and 30-84, their TnS mutants defective in phenazine production (Phz-), or the mutant strains genetically restored for phenazine production (Phz+) were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
149
0
4

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 345 publications
(157 citation statements)
references
References 46 publications
4
149
0
4
Order By: Relevance
“…No significant differential expression could be observed for the genes phnA and pqsA, and similar PQS and HHQ levels were shown under the applied test conditions. The phenazine pyocyanin is a heterocyclic redox-active pigment that exert toxic effects on other prokaryotes and eukaryotes (Mazzola et al, 1992;Mahajan-Miklos et al, 1999), and is produced in response to PQS signalling (Déziel et al, 2004). Recently, Dietrich and colleagues (2006) demonstrated that pyocyanin acts as a terminal signalling molecule in the PQScontrolled QS pathway.…”
Section: Discussionmentioning
confidence: 99%
“…No significant differential expression could be observed for the genes phnA and pqsA, and similar PQS and HHQ levels were shown under the applied test conditions. The phenazine pyocyanin is a heterocyclic redox-active pigment that exert toxic effects on other prokaryotes and eukaryotes (Mazzola et al, 1992;Mahajan-Miklos et al, 1999), and is produced in response to PQS signalling (Déziel et al, 2004). Recently, Dietrich and colleagues (2006) demonstrated that pyocyanin acts as a terminal signalling molecule in the PQScontrolled QS pathway.…”
Section: Discussionmentioning
confidence: 99%
“…PCA is produced in concentrations exceeding 1 mg g 21 root by rhizobacteria in dryland wheat fields throughout the low-precipitation zone of the Columbia Plateau, a major wheat-producing region in central Washington and Oregon, USA (Mavrodi et al, 2012a). Moreover, PCA has been shown to promote the colonization of wheat roots by fluorescent pseudomonads (Mazzola et al, 1992). However, PCA-producing (PCA 1 ) rhizobacteria are not abundant in irrigated fields or in highprecipitation areas within the Columbia Plateau (Mavrodi et al, 2012a,b;.…”
Section: Introductionmentioning
confidence: 99%
“…The most likely such benefit is suppression of nearby fungal or bacterial competitors. For strains such as Pseudomonas fluorescens 2-79 and P. aureofaciens 30-84, the production of phenazine antibiotics contributes to competitiveness on the roots of wheat (Mazzola et al 1992). In contrast, for P. fluorescens F113, the production of the antibiotic 2,4-diacetylphloroglucinol does not appear to be a factor in the competitiveness of the strain on the roots of sugarbeet (Carroll et al 1995).…”
Section: Special Featurementioning
confidence: 98%